FAMILY DAKWAH - Shubhan Hafidz (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2021)
Family Da'wah is a concept of da'wah which is being the foundation and guide in building an Islamic family. This concept actually aspires to form individuals as "best of created beings", because pious individuals are born from Islamic processes, ways of life and families. At the next level, these pious individuals will become milestones in building a family that’s blessed by Allah – Almighty. Because of the family is a miniature of society, – at its peak – we hope that these blessed families will manifest "the best of nations" as mandated by 110th verse of Surat Ali Imran, so that social problems that arise from individuals and families can be resolved properly according to the guidance of the revelation and guidance of the Prophet Muhammad (peace be upon him).